Kinetics of DNA Repair in Vicia faba Meristem Regeneration Following Replication Stress - Rybaczek, Dorota; Musiałek, Marcelina W; Vrána, Jan; Petrovská, Beáta; Pikus, Ewa G; Doležel, Jaroslav (Cells, 2021)
The astonishing survival abilities of Vicia faba, one the earliest domesticated plants, are associated, among other things, to the highly effective replication stress response system which ensures smooth cell division and proper preservation of genomic information. The most crucial pathway here seems to be the ataxia telangiectasia-mutated kinase (ATM)/ataxia telangiectasia and Rad3-related kinase (ATR)-dependent replication stress response mechanism, also present in humans. In this article, we attempted to take an in-depth look at the dynamics of regeneration from the effects of replication inhibition and cell cycle checkpoint overriding causing premature chromosome condensation (PCC) in terms of DNA damage repair and changes in replication dynamics. We were able to distinguish a unique behavior of replication factors at the very start of the regeneration process in the PCC-induced cells. We extended the experiment and decided to profile the changes in replication on the level of a single replication cluster of heterochromatin (both alone and with regard to its position in the nucleus), including the mathematical profiling of the size, activity and shape. The results obtained during these experiments led us to the conclusion that even "chaotic" events are dealt with in a proper degree of order.
Keywords: caffeine; Vicia faba; Chromosomes, Plant; DNA Repair; DNA damage; Stress, Physiological; DNA repair; nuclei sorting; fyziologický stres; DNA replication; Fluorescence; 5-ethynyl-2′-deoxyuridine; hydroxyurea; Regeneration; poškození DNA; Heterochromatin; Meristem; Kinetics; replication stress; DNA Damage; kinetika; regenerace; replikace DNA; DNA Replication; oprava DNA; meristém; heterochromatin; fluorescence; premature chromosome condensation; chromozomy rostlin